The diffusive-thermal instability of premixed flames with low unburned-gas temperature under the adiabatic and non-adiabatic conditions - Thwe Thwe AUNG (The Japan Society of Mechanical Engineers, 2015)
We elucidated the diffusive-thermal instability of premixed flames with low unburned-gas temperature under the adiabatic and non-adiabatic conditions. Numerical calculations of two-dimensional unsteady reactive flows were performed, based on the diffusive-thermal model equation. Lewis numbers smaller than unity were adopted, and radiative heat loss was treated. As the unburned-gas temperature became lower, the growth rate decreased and the unstable range narrowed, which was due to the decrease of the burning velocity of a planar flame. As for the growth rate and unstable range normalized by the burning velocity of a planar flame, the former increased and the latter widened. This was due to the enlargement of Zeldovich numbers. Taking account of radiative heat loss, the normalized growth rate was large and the normalized unstable range was wide. This indicated that the heat loss had a pronounced influence on the diffusive-thermal instability of premixed flames with low unburned-gas temperature. Moreover, the cellular-shape flame fronts formed owing to diffusive-thermal instability. The burning velocity of a cellular flame normalized by that of a planar flame increased as the unburned-gas temperature became lower and the heat loss became greater. This was because of the enlargement of Zeldovich numbers and the pronounced influence of heat loss.